Digital Tourism Analysis Based On Technology Acceptance Model (Tam) To Improve Tourist Destinations In Kerinci Regency - Ayu Esteka Sari (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyze the Technology Acceptance Model (TAM) in tourists in tourism areas in Kerinci Regency and to analyze the development of Digital Tourism with Technology Acceptance Model (TAM) in tourism areas in Kerinci Regency. This research using Structural Equation Modeling (SEM). Total sample of 100 respondents. The data used in this study were primary data through interviews and questionnaires. Data analysis in this study uses a structural equation model with the analysis tool used is to use AMOS. The results of the study : the Structural Equation Model (SEM) obtained from this study, it can be concluded from hypothesis testing. Perceived Enjoyment, Perceived Ease Of Use and Perceived Usefulness have a positive and significant effect on Intention to use tourism aplication in Kerinci Regency. while the Perceived Enjoyment, Perceived Ease Of Use and Intention to use tourism aplication have a positive and significant effect on Tourism Digital. But Perceived Usefulness has a negative and no significant effect on Tourism Digital.The Intention To Use Tourism Aplication can be explained by the variables Perceived Enjoyment, Perceived Ease Of Use and Perceived Usefulness of 25,2%. While Tourism Digital can be explained by the variability of Perceived Enjoyment, Perceived Ease Of Use, Perceived Usefulness and Intention To Use Tourism Aplication is 64,4%